2007
DOI: 10.1007/s00284-007-9009-4
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Are Present in Southern African Scorpions and Cluster with Supergroup F

Abstract: The presence and distribution of the intracellular bacteria Wolbachia in the arthropod subphylum Chelicerata (including class Arachnida) has not been extensively explored. Here we report the discovery of Wolbachia in scorpions. Five strains found in host species of the genus Opistophthalmus (Southern African burrowing scorpions) have been characterized by Multilocus Sequence Typing and by Wolbachia Surface Protein. Phylogenetic analyses indicate clustering in the supergroup F and a high genetic relatedness amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…Supergroup F is found in the subphyla Chelicerata and Hexapoda and also in the phylum Nematoda, indicating interhost transmission of Wolbachia between arthropods and nematodes (19,38). Trans- (6,16,29,43,63). This suggests multiple independent infections of the Chelicerata with Wolbachia.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Supergroup F is found in the subphyla Chelicerata and Hexapoda and also in the phylum Nematoda, indicating interhost transmission of Wolbachia between arthropods and nematodes (19,38). Trans- (6,16,29,43,63). This suggests multiple independent infections of the Chelicerata with Wolbachia.…”
Section: Discussionmentioning
confidence: 91%
“…For example, supergroup F was described in 2002 (34), yet the known diversity and geographic range of host species infected with the supergroup is rapidly expanding. It has been detected in both nematodes and several major arthropod orders (in Chelicerata, scorpions (6,19,20,34,38,45). Other host taxa for which there is evidence of infection by supergroup F are cockroaches (Blattodea) and ant lions (Neuroptera) (22,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable genetic diversity exists in Wolbachia, and gene phylogenies show the existence of 11 supergroups (A to K) (7,11,30,38,39). Studies of Wolbachia using multilocus sequence typing (MLST) have demonstrated discriminatory power of these approaches in accurately characterizing and identifying various Wolbachia strains (2,3,36,41,43,54,55). Wolbachia infections have been reported in various Lepidoptera families such as Lycaenidae, Pieridae, Nymphalidae, Hesperiidae, Pyralidae, Noctuidae, and Lasiocampidae (14,18,23,41,48).…”
mentioning
confidence: 99%
“…Supergroups A and B found in arthropods (36), supergroups C and D found in filarial nematodes (4), the E supergroup contain Wolbachia spp. from wingless insects, the springtails (Collembola) (35), members of supergroup F are known to infect arthropods (termites and scorpions) (3), and recent studies suggest that they also infect the filarial parasite Mansonella ozzardi, a causative agent of human filariasis (9,22), members in supergroup G infect spiders and members in supergroup H are found termites and also more recently Dipetalonema gracile included under the Group H (28,29).…”
Section: Introductionmentioning
confidence: 99%